(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The analysis of scientific literature shows that many domestic and foreign researchers have worked on the issues of reliability and safety of irrigation systems. The scientific solutions obtained by these researchers are presented in the form of scientific recommendations and regulatory criteria. However, despite this, some problems related to the reliability and safety of irrigation structures still remain unsolved. In particular, the issue of decreasing water transportation capacity in irrigation networks under variable hydraulic parameters of the water flow has not yet been resolved.